Discernir entre original y refundición en el teatro del Siglo de Oro a través de la estilometría: el caso de El mejor amigo, el muerto - Campión Larumbe, Miguel; Cuéllar, Álvaro (Talía. Revista de estudios teatrales, 2021)
Recasting is a recurring phenomenon in Spanish Golden Age theatre. There are numerous cases in which a playwright starts with a previous text and modifies it to form a new work by reusing a certain number of verses. Sometimes, with the passage of time, confusion is created between the original text and the recast version, and it becomes problematic to establish an order between the two versions. This is the case of El mejor amigo, el muerto, a play which has two textual variants that share a series of verses. Critics have argued that the handwritten version attributed to Belmonte, Rojas and Calderón constitutes the recasting of a previous text, transmitted by printed tradition. We propose here a protocol through stylometry to try to resolve this confusion and distinguish between original and recast. We apply it to our case study and propose that the version of these three playwrights appears to constitute the original text. In addition, we test the efficacy of stylometry in the problems of authorship of collaborated works and we attribute the questioned second act of the handwritten version to Francisco de Rojas Zorrilla.